Electrolytic capacitors
By optimizing the solid electrolyte layer distribution in distinct regions of the porous body, the electrolytic capacitor achieves reduced ESR and maintains capacity, addressing the insufficiency in existing capacitors.
Patent Information
- Application Number
- JP2023517514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-30
- Filing Date
- 2022-04-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-04-25
AI Technical Summary
Existing electrolytic capacitors face insufficient reduction in equivalent series resistance (ESR), particularly in high-temperature environments.
The electrolytic capacitor design includes a porous body with distinct regions: a first region near the surface and a second region closer to the center, where the filling rate of the solid electrolyte layer in the second region is 1/10 or less than in the first region, optimizing the distribution to enhance conductivity and reduce ESR.
This design effectively reduces ESR by improving current flow efficiency through the solid electrolyte layer and metal skeleton, achieving lower ESR while maintaining capacity.
Smart Images

Figure 0007603232000003 
Figure 0007603232000004 
Figure 0007603232000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic capacitor. [Background technology]
[0002] In recent years, electrolytic capacitors with small equivalent series resistance (ESR) and excellent frequency characteristics have been developed. The electrolytic capacitor includes an anode body having a porous body containing a valve metal and a dielectric layer covering the porous body, and a solid electrolyte layer that fills the pores of the porous body and covers the dielectric layer.
[0003] Patent Document 1 proposes a solid electrolytic capacitor in which the thickness of the conductive polymer layer in the center of the capacitor element is at least 0.02 μm to 0.14 μm. Patent Document 1 also proposes that in the solid electrolytic capacitor, the difference between the thickness of the conductive polymer layer in the center of the capacitor element and the thickness of the conductive polymer layer in the vicinity of the outer surface of the capacitor element should be within 0.08 μm. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-87177 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for reducing the ESR of electrolytic capacitors. In the electrolytic capacitor described in Patent Document 1, the increase in ESR in a high-temperature environment is suppressed, but the reduction in ESR of electrolytic capacitors is still insufficient. [Means for solving the problem]
[0006] One aspect of the present invention relates to an electrolytic capacitor including an anode body having a porous body containing a valve action metal and a dielectric layer covering the porous body, and a solid electrolyte layer filled in pores of the porous body and covering the dielectric layer, the porous body having a first region on an outer surface side of the porous body and a second region other than the first region, the first region being a region that is closer to the outer surface of the porous body than 0.5D when the shortest distance from the outer surface to a center of the porous body is D, a packing rate of the solid electrolyte layer in the porous body is smaller in the second region than in the first region, and a ratio R2 / R1 of a packing rate R1 of the solid electrolyte layer in the first region to a packing rate R2 of the solid electrolyte layer in the second region is 1 / 10 or less. Effect of the Invention
[0007] According to the present invention, an electrolytic capacitor with low ESR can be provided.
[0008] The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view illustrating an example of an electrolytic capacitor according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of an anode body having a solid electrolyte layer formed on the surface thereof. [Diagram 3] FIG. 2 is a cross-sectional view showing a first region and a second region of a porous body. [Figure 4] FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the following, an embodiment of the electrolytic capacitor according to the present disclosure will be described by way of example, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present disclosure are obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "numerical value A or more and numerical value B or less." In the following description, when a lower limit and an upper limit of a numerical value related to a specific physical property or condition are exemplified, any of the exemplified lower limits and any of the exemplified upper limits can be arbitrarily combined as long as the lower limit is not equal to or greater than the upper limit. When multiple materials are exemplified, one of them may be selected and used alone, or two or more of them may be used in combination.
[0011] The present disclosure also encompasses any combination of features recited in any two or more claims arbitrarily selected from the multiple claims recited in the accompanying claims, i.e., any combination of features recited in any two or more claims arbitrarily selected from the multiple claims recited in the accompanying claims may be used unless a technical contradiction arises.
[0012] The term "electrolytic capacitor" may be read as a "solid electrolytic capacitor", and the term "capacitor" may be read as a "capacitor".
[0013] An electrolytic capacitor according to an embodiment of the present invention includes an anode body having a porous body containing a valve metal and a dielectric layer covering the porous body, and a solid electrolyte layer that fills the pores of the porous body and covers the dielectric layer. Hereinafter, the anode body and the solid electrolyte layer together (or the anode body, the solid electrolyte layer, and the cathode layer described below together) are also referred to as a capacitor element. The porous body has a first region on the outer surface side of the porous body and a second region other than the first region. The first region is a region that is closer to the outer surface of the porous body than 0.5D, where D is the shortest distance from the outer surface to the center of the porous body.
[0014] The packing rate of the solid electrolyte layer in the porous body is smaller in the second region than in the first region, and the ratio R2 / R1 of the packing rate R1 of the solid electrolyte layer in the first region to the packing rate R2 of the solid electrolyte layer in the second region is 1 / 10 or less. In this case, the ESR of the electrolytic capacitor can be reduced.
[0015] In the first region (the outer surface side of the porous body) where a large amount of current flows, the solid electrolyte layer is filled in a large amount, improving the conductivity. As a result, many conductive paths are formed through the solid electrolyte layer filled in the pores of the porous body, and current flows efficiently between the metal skeletons through the solid electrolyte layer filled in the pores of the porous body as well as through the metal skeletons that constitute the porous body. On the other hand, in the second region (the center side of the porous body), the filling amount of the solid electrolyte layer is suppressed to an extent that the capacity can be secured, so that the current easily flows through the low-resistance metal skeleton that constitutes the porous body, and the increase in resistance due to the current flowing through the solid electrolyte layer is suppressed. When R2 / R1 is 1 / 10 or less, the above-mentioned actions in the first region and the second region work together to effectively reduce the ESR.
[0016] From the viewpoint of easily reducing the ESR, R2 / R1 is preferably 3 / 100 or less, and more preferably 1 / 100 or less. From the viewpoint of easily ensuring the capacity, R2 / R1 is preferably 1 / 1000 or more, and more preferably 3 / 1000 or more. From the viewpoint of reducing the ESR and ensuring the capacity, the range of R2 / R1 may be 1 / 1000 or more and 1 / 10 or less, 1 / 1000 or more and 3 / 100 or less, or 1 / 1000 or more and 1 / 100 or less.
[0017] From the viewpoint of facilitating reduction of ESR, R1 is preferably 80% or more. Similarly, R2 is preferably 9% or less, and more preferably 2.5% or less. From the viewpoint of ensuring capacity, R2 may be 0.08% or more, or may be 0.25% or more.
[0018] The filling rate R (%) of the solid electrolyte layer means the ratio of the area of the solid electrolyte layer to the area of voids (holes in the anode body) in a cross section of the anode body observed with an electron microscope (a cross section including a line segment defining the shortest distance D). The area of the voids in the cross section means the value obtained by subtracting the area of the anode body (the total of the porous body and the dielectric layer) in the cross section from the total area of the cross section. A scanning electron microscope (SEM) or a transmission electron microscope (TEM) can be used as the electron microscope.
[0019] The above R1 and R2 can be determined by the following method. The electrolytic capacitor is disassembled, and the capacitor element is taken out and processed with a cross-section polisher (CP) to obtain a sample cross-section for SEM observation. The sample cross-section (cross-section of the anode body) is observed by SEM, and an image (for example, magnification: 100 times to 100,000 times) is obtained. From the SEM image, the area S0 (for example, 0.9 μm 2 ~1000μm 2 ), the area S1 occupied by the anode body (the sum of the porous body and the dielectric layer), and the area S2 occupied by the solid electrolyte layer are calculated. The filling rate R (%) is calculated as {S2 / (S0-S1)} x 100. The value obtained by subtracting S1 from S0 is the area occupied by voids.
[0020] The packing ratio R1 of the solid electrolyte layer in the first region is obtained by calculating the packing ratio R for any number of regions (for example, 3 to 5 regions) at any depth of the first region using SEM images, and calculating the maximum value among them. At least one of the above-mentioned several regions is included in the vicinity of the outer surface of the porous body. Note that the vicinity of the outer surface of the porous body means a region that is closer than 0.2D from the outer surface of the porous body. The packing ratio of the solid electrolyte layer in the vicinity of the outer surface of the porous body can be R1. For example, when 0.5D is 225 μm to 410 μm, the centers of the above-mentioned three regions can be near the outer surface of the porous body (near 0 μm), at a depth of 50 μm from the outer surface, and at a depth of 100 μm from the outer surface.
[0021] The filling rate R2 of the solid electrolyte layer in the second region is obtained by calculating the filling rate R for any number of regions (for example, 3 to 5 regions) at any depth in the second region using SEM images and calculating the average value. At least one of the above-mentioned several regions is included in the vicinity of the center of the porous body. Note that the vicinity of the center of the porous body means a region that is closer than 0.2D from the center of the porous body. When an anode wire described later is present in the center of the porous body, the vicinity of the center of the porous body means the vicinity of the anode wire. The filling rate of the solid electrolyte layer in the vicinity of the center of the porous body can be R2. In the above, the observation of the sample cross section is performed by SEM, but it may also be performed by TEM.
[0022] From the filling rate R obtained for any number of regions at any depth in the first and second regions, it can be confirmed that the filling rate R is smaller in the second region than in the first region.
[0023] From the viewpoint of easily obtaining the effect of reducing ESR by making R2 / R1 1 / 10 or less, the conductivity of the solid electrolyte layer is preferably 15 S / cm or more (or 20 S / cm or more) and 500 S / cm or less, more preferably 15 S / cm or more (or 20 S / cm or more) and 300 S / cm or less. Similarly, the conductivity of the solid electrolyte layer is further preferably 15 S / cm or more (or 20 S / cm or more) and 200 S / cm or less, and particularly preferably 15 S / cm or more (or 20 S / cm or more) and 150 S / cm or less.
[0024] From the viewpoint of reducing ESR and ensuring capacity, when the electrical conductivity of the solid electrolyte layer is 15 S / cm or more (or 20 S / cm or more) and 150 S / cm or less, R1 may be 80% or more, and R2 / R1 may be 1 / 1000 or more and 1 / 10 or less (preferably 1 / 100 or more and 1 / 10 or less).
[0025] Similarly, when the conductivity of the solid electrolyte layer is greater than 150 S / cm and less than 200 S / cm, R1 may be 80% or more, and R2 / R1 may be 1 / 1000 or more and less than 1 / 10 (preferably 1 / 100 or more and less than 1 / 10).
[0026] Similarly, when the conductivity of the solid electrolyte layer is greater than 200 S / cm and less than 300 S / cm, R1 may be 80% or more, and R2 / R1 may be 1 / 1000 or more and less than 3 / 100 (preferably 1 / 100 or more and less than 3 / 100).
[0027] Similarly, when the electrical conductivity of the solid electrolyte layer is more than 300 S / cm and not more than 500 S / cm, R1 may be 80% or more, and R2 / R1 may be 1 / 1000 or more and less than 1 / 100.
[0028] The electrical conductivity of the solid electrolyte layer can be determined by the following method. The electrolytic capacitor is disassembled, the capacitor element is taken out, and the components of the solid electrolyte layer are analyzed. When the solid electrolyte layer is formed using the first or second treatment liquid, the components of the first or second treatment liquid may be analyzed. Examples of the analysis method that can be used include TEM (transmission electron microscope)-EELS (electron energy loss spectroscopy), NMR (nuclear magnetic resonance spectroscopy), and Raman spectroscopy.
[0029] Based on the analysis results, a sample film (e.g., 20 μm to 40 μm thick) containing the same components as the solid electrolyte layer is formed, and the conductivity of the sample film is determined as the conductivity of the solid electrolyte layer. The Loresta-GX and PSP probe manufactured by Nitto Seiko Analytech Co., Ltd. can be used as the conductivity measuring device.
[0030] When the solid electrolyte layer is formed using the first or second treatment liquid described below, the sample film may be formed using the first or second treatment liquid described below. When the solid electrolyte layer is composed of the first and second layers described below, the sample film may be formed having a laminated structure of the first and second layers similar to that of the solid electrolyte layer. The thickness ratio of the first and second layers in the sample film may be appropriately determined according to the thickness ratio T2 / T1 described below. The thickness T1 can be regarded as the total thickness of the first and second layers. The thickness T2 can be regarded as the thickness of the first layer.
[0031] The ratio T2 / T1 of the thickness T2 of the solid electrolyte layer in the vicinity of the center of the porous body (the region closer than 0.2D from the center) to the thickness T1 of the solid electrolyte layer in the vicinity of the outer surface of the porous body (the region closer than 0.2D from the outer surface) is, for example, 0.1 or less, and may be 0.01 or more and 0.1 or less. The thickness T2 of the solid electrolyte layer in the vicinity of the center of the porous body is, for example, less than 0.02 μm (or 0.017 μm or less). The solid electrolyte layer with the thickness T1 can be formed, for example, by the first layer and the second layer described later. The solid electrolyte layer with the thickness T2 can be formed, for example, by the first layer described later.
[0032] The thickness T1 of the solid electrolyte layer is obtained by obtaining an SEM image of the cross section of the sample in the same manner as in obtaining R1 and R2, measuring the thickness at any 10 points near the outer surface of the porous body using the image, and calculating the average value of the measured values. The thickness T2 of the solid electrolyte layer is obtained by measuring the thickness at any 10 points near the center of the porous body, and calculating the average value of the measured values.
[0033] (Porous body) The porous body contains a valve metal, such as aluminum (Al), titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), or hafnium (Hf).
[0034] As the porous body, for example, a sintered body of a compact of raw material particles (raw material powder) containing a valve metal is used. The particles may be particles of a valve metal, particles of an alloy containing a valve metal, or particles of a compound containing a valve metal. The particles may be of one type or a mixture of two or more types.
[0035] The porous body can be obtained, for example, by pressurizing raw material particles into a predetermined shape to obtain a molded body, and then sintering the molded body. For example, an anode wire may be placed at a predetermined position in a mold, raw material particles may be introduced into the mold, and the molded body may be pressurized to obtain a molded body. The molded body may be sintered to obtain a porous body in which a part of the anode wire is embedded. The porous body is usually a rectangular parallelepiped.
[0036] (anode wire) The anode body may include a rod-shaped anode wire partially embedded in the porous body. A portion of the anode wire may be embedded in the porous body so as to pass through the center of the porous body. When the porous body is a rectangular parallelepiped, the anode wire is planted from one end face of the rectangular parallelepiped. The anode wire may include a valve metal. A portion of the anode wire is embedded in the porous body, and the remainder protrudes from the porous body. The remainder is connected to an anode lead terminal by welding or the like.
[0037] (Dielectric layer) The dielectric layer is formed so as to cover the outer surface of the porous body and the inner wall surface of the pores of the porous body. The dielectric layer is formed, for example, by subjecting the porous body to a chemical conversion treatment and growing an oxide film on the surface of the porous body. The chemical conversion treatment may be performed by immersing the porous body in a chemical conversion solution to anodize the surface of the porous body. Alternatively, the surface of the porous body may be oxidized by heating the porous body in an atmosphere containing oxygen.
[0038] (Solid electrolyte layer) The solid electrolyte layer is disposed so as to cover at least a part of the dielectric layer. The solid electrolyte layer may be filled in the pores of the porous body via the dielectric layer and formed on the outer surface of the porous body. The solid electrolyte layer may be a laminate of two or more different solid electrolyte layers.
[0039] The solid electrolyte layer includes, for example, a conductive polymer. The conductive polymer may be a π-conjugated polymer, and examples of the conductive polymer include polypyrrole, polythiophene, polyaniline, and derivatives thereof. These may be used alone or in combination. The conductive polymer may be a copolymer of two or more monomers. The derivative of a conductive polymer means a polymer having a conductive polymer as a basic skeleton. For example, an example of a polythiophene derivative includes poly(3,4-ethylenedioxythiophene) (PEDOT).
[0040] A dopant may be added to the conductive polymer. That is, the solid electrolyte layer may include a conductive polymer and a dopant. The conductive polymer may be included in the solid electrolyte layer in a state where the dopant is doped. The dopant may be selected according to the conductive polymer, and a known dopant may be used. Examples of the dopant include benzenesulfonic acid, alkylbenzenesulfonic acid, naphthalenesulfonic acid, alkylnaphthalenesulfonic acid, polystyrenesulfonic acid (PSS), and salts thereof. The solid electrolyte layer may include, for example, PEDOT doped with PSS.
[0041] The solid electrolyte layer containing a conductive polymer can be formed, for example, by impregnating a porous body (anode body) having a dielectric layer formed on its surface with a first treatment liquid containing a monomer (or oligomer), and then polymerizing the monomer (or oligomer) by chemical polymerization or electrolytic polymerization. In the case of chemical polymerization, the first treatment liquid contains, for example, a monomer (or oligomer), an oxidizing agent, and a solvent (or dispersion medium). Examples of the monomer include 3,4-ethylenedioxythiophene (EDOT) and pyrrole. The first treatment liquid may contain a dopant.
[0042] Alternatively, the solid electrolyte layer may be formed by impregnating a porous body (anode body) having a dielectric layer formed on its surface with a second treatment liquid containing a conductive polymer, and drying the second treatment liquid. The second treatment liquid contains, for example, a conductive polymer, a solvent (or a dispersion medium), and, if necessary, a dopant.
[0043] The conductivity of the solid electrolyte layer can be adjusted by, for example, changing the conductive polymer, dopant, polymerization conditions (polymerization method, oxidizing agent, etc.), and the like.
[0044] The process of forming the solid electrolyte layer may include a first process of forming a thin solid electrolyte layer (hereinafter also referred to as the first layer) having a small thickness in the first region and the second region, and a second process of forming a thick solid electrolyte layer (hereinafter also referred to as the second layer) in the first region (particularly in the vicinity of the outer surface of the porous body) after the first process. In this case, it is easy to control R2 / R1 to 1 / 10 or less. It is easy to control R1 to a filling rate based on the sum of the first layer and the second layer. It is easy to control R2 to a filling rate based on the first layer. The components (conductive polymer, dopant, etc.) contained in the first layer and the second layer may be the same or different from each other.
[0045] In the first step, the chemical polymerization may be carried out at a low temperature (for example, 10° C. or lower, within a temperature range in which chemical polymerization is possible). In this case, diffusion of the first treatment liquid (polymerization liquid) is suppressed, and a solid electrolyte layer having a small thickness is likely to be formed in the first region and the second region.
[0046] In the second step, electrolytic polymerization may be performed so that a second layer having a large thickness is formed in the first region. For example, electrolytic polymerization may be performed in a plurality of steps by changing the current value. For example, step (2a) of electrolytic polymerization with a large current may be performed, and after step (2a), step (2b) of electrolytic polymerization with a small current for a relatively long time may be performed. In step (2a), a second layer having a large thickness may be formed to some extent in the first region so as to block the pores of the porous body. Thus, the formation of the second layer in step (2b) is performed in the first region and suppressed in the second region. As a result, by performing electrolytic polymerization with a small current for a relatively long time in step (2b), the filling rate of the solid electrolyte layer in the first region can be sufficiently increased so that R2 / R1 is 1 / 10 or less.
[0047] (others) The capacitor element may include a cathode layer covering at least a portion of the solid electrolyte layer. The electrolytic capacitor may include an anode lead terminal and a cathode lead terminal electrically connected to the capacitor element, and an exterior resin arranged around the capacitor element. The cathode lead terminal is connected to the cathode part via a conductive member. The anode lead terminal is connected to an end of the anode wire protruding from the porous body. The shape, size, etc. of the capacitor element are not particularly limited, and may be a known capacitor element or a capacitor element having a similar configuration.
[0048] (cathode layer) The cathode layer may include a carbon layer formed on the solid electrolyte layer and a metal paste layer formed on the carbon layer. The carbon layer may be formed of a conductive carbon material such as graphite and a resin. The metal paste layer may be formed of metal particles (e.g., silver particles) and a resin, for example, a known silver paste.
[0049] (Conductive material) The cathode layer is connected to the connection portion of the cathode lead terminal by a conductive member. That is, the cathode layer (cathode portion) is electrically connected to the cathode lead terminal. The conductive member is made of a material having electrical conductivity. The conductive member may be formed using a material containing metal particles (e.g., silver particles) and a resin, and may be formed using, for example, a known metal paste (e.g., silver paste). The conductive member is formed by heating the metal paste. The conductive member may be made of a plurality of conductive layers of different types.
[0050] (Exterior resin) The exterior resin is disposed around the capacitor element so that the capacitor element is not exposed on the surface of the electrolytic capacitor. Furthermore, the exterior resin insulates the anode lead terminal and the cathode lead terminal. The exterior resin may be a known exterior resin used for electrolytic capacitors. For example, the exterior resin may be formed using an insulating resin material used for sealing the capacitor element. The exterior resin may be formed by placing the capacitor element in a mold, and introducing an uncured thermosetting resin and a filler into the mold by a transfer molding method, a compression molding method, or the like, and curing the resin.
[0051] Examples of the exterior resin include epoxy resin, phenolic resin, silicone resin, melamine resin, urea resin, alkyd resin, polyurethane, polyimide, unsaturated polyester, etc. The exterior resin may contain substances other than resin (such as inorganic filler).
[0052] (Cathode lead terminal) A part of the cathode lead terminal is exposed from the exterior resin and used as a cathode external terminal. The material of the cathode lead terminal may be any material that can be used as a material of a cathode lead terminal of an electrolytic capacitor. For example, a known material of a cathode lead terminal used in an electrolytic capacitor may be used. The cathode lead terminal may be formed by processing a metal sheet (including a metal plate and a metal foil) made of a metal (copper, copper alloy, etc.) by a known metal processing method.
[0053] (Anode lead terminal) A part of the anode lead terminal is exposed from the exterior resin and used as an anode external terminal. The material of the anode lead terminal may be any material that can be used as a material of an anode lead terminal of an electrolytic capacitor. For example, a known material of an anode lead terminal used in an electrolytic capacitor may be used. The anode lead terminal may be formed by processing a metal sheet (including a metal plate and a metal foil) made of a metal (copper, copper alloy, etc.) by a known metal processing method.
[0054] FIG. 1 is a cross-sectional view showing an example of an electrolytic capacitor according to the present embodiment. FIG. 2 is a cross-sectional view showing an anode body having a solid electrolyte layer formed on the surface. FIG. 3 is a cross-sectional view showing a first region and a second region of a porous body. FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. 3. FIGS. 3 and 4 are cross-sectional views including the center C of the porous body. Note that each drawing is a schematic view, and the ratio of dimensions (length, width, thickness, etc.) of each component may not necessarily be the same as the actual ones.
[0055] Electrolytic capacitor 20 includes capacitor element 10, exterior resin 11 that seals capacitor element 10, and anode lead terminal 12 and cathode lead terminal 13 that are electrically connected to capacitor element 10. Anode lead terminal 12 and cathode lead terminal 13 are each partially exposed from exterior resin 11. Anode lead terminal 12 and cathode lead terminal 13 are partially covered by exterior resin 11 together with capacitor element 10.
[0056] Capacitor element 10 includes an anode body 1, a solid electrolyte layer 2 formed on the anode body 1, and a cathode layer 3 formed on the solid electrolyte layer 2. The anode body 1 includes a porous body 4 containing a valve metal, and a dielectric layer 5 covering the porous body 4. The dielectric layer 5 is formed so as to cover the outer surface S of the porous body 4 and the inner wall surfaces of the holes 7. The anode body 1 has approximately the same porous shape as the porous body 4.
[0057] The porous body 4 has a substantially rectangular parallelepiped shape and has six side surfaces. A part of the anode wire 6 extends from one side surface of the porous body 4. That is, the anode wire 6 has a first portion 6a embedded in the porous body 4 from one side surface of the porous body 4, and a second portion 6b extending from one side surface of the porous body 4. The second portion 6b is joined to the anode lead terminal 12 by welding or the like. In this embodiment, the first portion 6a is embedded in the porous body 4 so as to pass through the center C of the porous body 4, but it may be embedded in the porous body 4 so as not to pass through the center C of the porous body 4.
[0058] The solid electrolyte layer 2 is formed so as to cover at least a portion of the dielectric layer 5. The solid electrolyte layer 2 is filled in the holes 7 of the porous body 4 (anode body 1). The solid electrolyte layer 2 is formed so as to cover the outer surface S of the porous body 4 and the inner wall surfaces of the holes 7 with the dielectric layer 5 interposed therebetween.
[0059] As shown in Figures 3 and 4, the porous body 4 has a first region 4a on the outer surface side of the porous body 4 and a second region 4b other than the first region 4a. The first region 4a is a region (shaded area in Figures 3 and 4) that is closer than 0.5D from the outer surface S of the porous body 4, where D is the shortest distance from the outer surface S to the center C of the porous body 4. The packing rate of the solid electrolyte layer 2 in the porous body 4 is smaller in the second region 4b than in the first region 4a. The ratio R2 / R1 of the packing rate R2 of the solid electrolyte layer 2 in the second region 4b to the packing rate R1 of the solid electrolyte layer 2 in the first region 4a is 1 / 10 or less.
[0060] The cathode layer 3 is formed so as to cover the surface of the solid electrolyte layer 2. The cathode layer 3 has a carbon layer 3a formed so as to cover the solid electrolyte layer 2, and a metal paste layer 3b formed on the surface of the carbon layer 3a. The cathode lead terminal 13 is joined to the cathode layer 3 (metal paste layer 3b) via a conductive member 8. The carbon layer 3a contains a conductive carbon material such as graphite and a resin. The metal paste layer 3b contains, for example, metal particles (e.g., silver) and a resin. The configuration of the cathode layer 3 is not limited to this configuration. The cathode layer 3 may have any configuration as long as it has a current collecting function.
[0061] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0062] Examples 1 to 6 (Preparation of porous bodies) One end of the anode wire was embedded in the Ta particles to form the Ta particles into a rectangular parallelepiped, and the formed body was then sintered in a vacuum. In this way, a porous body (Ta sintered body) in which a part of the anode wire was embedded was obtained. The shortest distance D from the outer surface to the center of the porous body was 450 μm. Ta wire was used as the anode wire.
[0063] (Formation of dielectric layer) The porous body with the anode wire partially embedded therein was immersed in an anodization tank filled with an aqueous phosphoric acid solution, which is an aqueous electrolytic solution, and anodization was performed. In this manner, an oxide film (dielectric layer) was formed on the surface of the porous body. In the anodization, the phosphoric acid concentration can be appropriately selected within the range of 0.01 to 5 mass%, the anodization voltage can be selected within the range of 2 to 100 V, and the temperature can be selected within the range of 20 to 80°C.
[0064] (Formation of solid electrolyte layer) (1st step) First, a thin first layer (conductivity 21 S / cm) containing polypyrrole and a dopant was formed in the first and second regions of a porous body having a dielectric layer on the surface (first step). A sulfonate having a naphthalene skeleton was used as the dopant. The first layer was formed by chemical polymerization. The chemical polymerization was performed using a treatment liquid containing pyrrole, a dopant, an oxidizing agent, and water. The first layer was formed thinly in the first and second regions by performing chemical polymerization at a low temperature (within the temperature range where chemical polymerization is possible at 10°C or less), and the thickness T2 of the solid electrolyte layer near the center of the porous body was set to the value shown in Table 1.
[0065] (2nd process) Next, a second layer (conductivity 21 S / cm) containing polypyrrole and a dopant was formed thickly in the first region of the porous body having a dielectric layer on the surface (second process). The dopant used was the same as that used to form the first layer. The second layer was formed by electrolytic polymerization. The electrolytic polymerization was performed using a treatment solution containing pyrrole, dopant, and water. Step (2a) of electrolytic polymerization at a large current was performed at 25°C, and after step (2a), step (2b) of electrolytic polymerization at a small current for a relatively long time was performed. As a result, the second layer was formed thickly in the first region, and the thickness T1 of the solid electrolyte layer near the outer surface of the porous body was set to the value shown in Table 1.
[0066] In this way, in the second region, a solid electrolyte layer was formed almost entirely from the first layer. In the first region (particularly on the outer surface side of the porous body), a solid electrolyte layer was formed from the first layer and the second layer. In this way, the solid electrolyte layer was formed so that the packing rate of the solid electrolyte layer in the porous body was smaller in the second region than in the first region. The electrical conductivity of the solid electrolyte layer was 21 S / cm.
[0067] In the above, the temperature during chemical polymerization in the first step (first layer formation step) was adjusted to set the packing rate R2 of the solid electrolyte layer in the second region to the value shown in Table 1. The magnitude of the current and the time for which the current was passed during electrolytic polymerization in the second step (second layer formation step) were adjusted to set the packing rate R1 of the solid electrolyte layer in the first region to the value shown in Table 1.
[0068] The packing ratio R1 of the solid electrolyte layer in the first region and the packing ratio R2 of the solid electrolyte layer in the second region were determined by the method described above when the solid electrolyte layer was formed. The thickness T1 of the solid electrolyte layer near the outer surface of the porous body and the thickness T2 of the solid electrolyte layer near the center of the porous body were also determined by the method described above. The determined T1 and T2 values are shown in Table 1.
[0069] (Formation of cathode layer) A dispersion of carbon particles (carbon paste) was applied to the solid electrolyte layer and heated to form a carbon layer on the surface of the solid electrolyte layer. A metal paste containing silver particles, a binder resin, and a solvent was applied to the surface of the carbon layer and heated to form a metal paste layer, thereby obtaining a cathode layer composed of the carbon layer and the metal paste layer. In this way, a capacitor element was obtained.
[0070] (Making electrolytic capacitors) A conductive adhesive that serves as a conductive member was applied to the metal paste layer, and the cathode lead terminal and the metal paste layer were bonded. The anode wire and the anode lead terminal were bonded by resistance welding. Next, the capacitor element to which each lead terminal was bonded was sealed with an exterior resin. In this way, an electrolytic capacitor was obtained. In Table 1, X1 to X6 represent the electrolytic capacitors of Examples 1 to 6, respectively.
[0071] Comparative Example 1 In the second step of the solid electrolyte layer formation process, electrolytic polymerization was performed at 25°C with a small current for a relatively long time (by not performing step (2a)), so that a second layer was formed to some extent also in the second region (near the center of the porous body), and the thickness T2 of the solid electrolyte layer near the center of the porous body was set to the value shown in Table 1. The packing ratio R2 of the solid electrolyte layer in the second region was set to the value shown in Table 1, and R2 / R1 was set to 3 / 10.
[0072] Except for the above, electrolytic capacitor Y1 was produced in the same manner as electrolytic capacitor X1 of Example 1.
[0073] [Rating 1] For each electrolytic capacitor obtained above, the capacitance (μF) at a frequency of 120 Hz and the ESR (mΩ) at a frequency of 100 kHz were measured using a four-terminal LCR meter in an environment of 20°C. The capacitance was expressed as a relative value when the capacitance of Y1 was taken as 100, and a capacitance of 75 or more was evaluated as good. The evaluation results are shown in Table 1.
[0074] [Table 1]
[0075] The electrolytic capacitors X1 to X6 had a lower ESR than the electrolytic capacitor Y1. The electrolytic capacitors X1 to X5 had a good capacitance.
[0076] Examples 7 to 9 The electrical conductivity of the solid electrolyte layer was set to the value shown in Table 2. The electrical conductivity of the solid electrolyte layer was adjusted by changing the type of dopant used in forming the first layer and the second layer. Except for the above, electrolytic capacitors X7 to X9 of Examples 7 to 9 were produced in the same manner as electrolytic capacitor X1 of Example 1, respectively.
[0077] Comparative Examples 2 to 4 The electrical conductivity of the solid electrolyte layer was set to the value shown in Table 2. The electrical conductivity of the solid electrolyte layer was adjusted by changing the type of dopant used in forming the first layer and the second layer. Except for the above, electrolytic capacitors Y7 to Y9 of Comparative Examples 2 to 4 were produced in the same manner as electrolytic capacitor Y1 of Comparative Example 1, respectively.
[0078] Examples 10 to 13 The solid electrolyte layer was formed as follows. (1st step) First, a thin first layer containing PEDOT and a dopant was formed in the first and second regions of a porous body having a dielectric layer on its surface (first step). The first layer was formed by chemical polymerization. The chemical polymerization was performed using a treatment liquid containing EDOT, a dopant, an oxidizing agent, and water. The first layer was formed thinly in the first and second regions by performing chemical polymerization at a low temperature (within the temperature range where chemical polymerization is possible below 10°C).
[0079] (2nd process) Next, a second layer containing PEDOT and a dopant was formed thickly in the first region of the porous body having a dielectric layer on its surface (second process). The dopant used was the same as that used to form the first layer. The second layer was formed by electrolytic polymerization. The electrolytic polymerization was performed using a treatment liquid containing EDOT, a dopant, and water. Step (2a) of electrolytic polymerization at a large current was performed at 25°C, and after step (2a), step (2b) of electrolytic polymerization at a small current for a relatively long time was performed, thereby forming a thick second layer in the first region.
[0080] The electrical conductivity of the solid electrolyte layer was set to the value shown in Table 2. The electrical conductivity of the solid electrolyte layer was adjusted by changing the type of dopant used in forming the first layer and the second layer.
[0081] In this way, in the second region, the solid electrolyte layer was formed almost entirely from the first layer. In the first region (particularly on the outer surface side of the porous body), the solid electrolyte layer was formed from the first layer and the second layer. In this way, the solid electrolyte layer was formed so that the packing rate of the solid electrolyte layer in the porous body was smaller in the second region than in the first region.
[0082] In the above, the temperature during chemical polymerization in the first step (first layer formation step) was adjusted to set the packing rate R2 of the solid electrolyte layer in the second region to 0.25%. The magnitude of the current and the time for which the current was passed during electrolytic polymerization in the second step (second layer formation step) were adjusted to set the packing rate R1 of the solid electrolyte layer in the first region to 84%. R2 / R1 was 3 / 1000. The thickness T1 of the solid electrolyte layer near the outer surface of the porous body was 170 nm. The thickness T2 of the solid electrolyte layer near the center of the porous body was 0.51 nm.
[0083] Except for the above, electrolytic capacitors X10 to X13 of Examples 10 to 13 were fabricated in the same manner as electrolytic capacitor X1 of Example 1, respectively.
[0084] Comparative Examples 5 to 8 In the second step of the solid electrolyte layer formation process, electrolytic polymerization was performed at 25° C. for a relatively long time with a small current (by not performing step (2a)), so that the second layer was formed to some extent in the second region (near the center of the porous body). The thickness T2 of the solid electrolyte layer near the center of the porous body was 51 nm, the filling rate R2 of the solid electrolyte layer in the second region was 25%, and R2 / R1 was 3 / 10.
[0085] Except for the above, electrolytic capacitors Y10 to Y13 of Comparative Examples 5 to 8 were fabricated in the same manner as electrolytic capacitors X10 to X13 of Examples 10 to 13, respectively.
[0086] [Rating 2] The ESR of each electrolytic capacitor was measured by the same method as in Evaluation 1. Furthermore, based on the measurement results, the degree of ESR reduction by keeping the conductivity of the solid electrolyte layer constant and changing R2 / R1 from 3 / 10 to 3 / 1000 was examined. Specifically, when the ESR of an electrolytic capacitor with R2 / R1 of 3 / 1000 and an electrolytic capacitor with R2 / R1 of 3 / 10, which have the same conductivity of the solid electrolyte layer, are x and y, respectively, x / y was obtained as the ESR ratio. For example, the ESR ratio in the case of electrolytic capacitor X1 means the ratio of the ESR value of electrolytic capacitor X1 to the ESR value of electrolytic capacitor Y1. The smaller the ESR ratio, the greater the effect of reducing ESR. The ESR ratio was obtained for each of electrolytic capacitors X1, X7 to X13. The evaluation results are shown in Table 2.
[0087] [Table 2]
[0088] The electrolytic capacitors X1, X7 to X13 exhibited lower ESR than the electrolytic capacitors Y1, Y7 to Y13, respectively. Among them, the electrolytic capacitors X1, X7 to X12, in which the conductivity of the solid electrolyte layer is 15 to 500 S / cm, had an ESR ratio of 0.95 or less, and showed an excellent effect of reducing the ESR by setting R2 / R1 to 1 / 10 or less. In particular, the electrolytic capacitors X1, X7 to X10, in which the conductivity of the solid electrolyte layer is 15 to 200 S / cm, had an ESR ratio of 0.87 or less, and showed a remarkable effect of reducing the ESR by setting R2 / R1 to 1 / 10 or less. [Industrial Applicability]
[0089] The present invention can be used in an electrolytic capacitor including a porous anode body and an anode wire partially embedded in the anode body. The electrolytic capacitor according to the present invention can be used in various applications requiring a low ESR.
[0090] Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be interpreted as limiting. Various variations and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be interpreted to cover all variations and modifications without departing from the true spirit and scope of the present invention. [Explanation of symbols]
[0091] 1: anode body, 2: solid electrolyte layer, 3: cathode layer, 3a: carbon layer, 3b: metal paste layer, 4: porous body, 4a: first region, 4b: second region, 5: dielectric layer, 6: anode wire, 6a: first portion, 6b: second portion, 7: hole, 8: conductive member, 10: capacitor element, 11: exterior resin, 12: anode lead terminal, 13: cathode lead terminal, 20: electrolytic capacitor
Claims
1. an anode body having a porous body containing a valve metal and a dielectric layer covering the porous body; a solid electrolyte layer that fills the pores of the porous body and covers the dielectric layer; Equipped with The porous body has a first region on an outer surface side of the porous body, and a second region that is in contact with the first region and is surrounded by the first region, The first region is a region from the outer surface of the porous body to a center thereof at a distance of 0.5D from the outer surface, where D is the shortest distance from the outer surface to the center of the porous body; a packing rate of the solid electrolyte layer in the porous body is smaller in the second region than in the first region, a ratio (R2 / R1) of a packing rate (R2) of the solid electrolyte layer in the second region to a packing rate (R1) of the solid electrolyte layer in the first region is 1 / 10 or less; An electrolytic capacitor, wherein R1 is 80% or more.
2. 2. The electrolytic capacitor according to claim 1, wherein R2 / R1 is equal to or greater than 1 / 1000 and equal to or less than 1 / 10.
3. 3. The electrolytic capacitor according to claim 2, wherein R2 / R1 is equal to or greater than 1 / 1000 and equal to or less than 3 / 100.
4. 4. The electrolytic capacitor according to claim 1, wherein R2 is 9% or less.
5. 4. The electrolytic capacitor according to claim 1, wherein the electrical conductivity of the solid electrolyte layer is 15 S / cm or more and 500 S / cm or less.
Citation Information
Patent Citations
Solid electrolytic capacitor
JP1992048710A
Solid electrolytic capacitor and its manufacture
JP1998321471A
Solid electrolytic capacitor and its manufacture
JP1999087177A
Solid electrolytic capacitor
JP2001110682A
Solid electrolytic capacitor and method of manufacturing the same
JP2009099974A
